PENGARUH KELENGKAPAN FASILITAS KAPAL DAN KETEPATAN WAKTU TERHADAP KEPUASAN PENUMPANG KAPAL PT. MARINA LOGISTIK SEJAHTERA BALIKPAPAN (STIE Rajawali Purworejo, 2021)
Passenger satisfaction is the main goal in a business or business, especially sea transportation services. To achieve passenger satisfaction, of course, there are many important aspects that must be met by service providers. Aspects that must be met include the completeness of the ship's facilities and timeliness. The related variables in this study are the completeness of ship facilities and timeliness of passenger satisfaction on PT. Marina Logistik Sejahtera with multiple linear regression analysis method. All statements were tested with validity, reliability and had a correlation > 0.300 (valid) and had an alpha coefficient > 0.6 (reliable). From the calculation of the coefficient of determination, the value of Adjusted